Nitrogen Fixation by some Ectomycorrhizal Fungi and Mycorrhizal Systems - Thapar, H. S.; Pokhriyal, T. C. (Indian Forester, 1993)
Nitrogenase-activity of six species of ectomycorrhizal fullgi I e. Pisolilhus tinclorius. Laccaria laccata, Cenococcum geophilum Syn Cenococclum graniforme Rhizopogon luteolus, Thelephora terrestris and Suillus brevipes in pure culture was assayed using Acetylene-Ethylene reduction technique in laboratory studies. All the six species showed a positive but variable response. Maximum activity was observed in Laccaria laccata followed by Suillus brevipes. The activity was minimal in case of Thelephora terrestris and Pisolithus tincforius. Mycorrhizal systems of Pinus patula showed 2-3 times higher nitrogenase activity as compan d to P. caribaea.